ANALISIS BUKU AJAR PAI DAN BUDI PEKERTI KELAS XI: PERSPEKTIF NILAI-NILAI PENDIDIKAN MULTIKULTURAL - Alif Masruri Abdul Haq; Teguh Prasetyo; Maulana Malik Ibrahim (Journal Multicultural of Islamic Education, 2026)
This study is motivated by the importance of cultivating an attitude of tolerance, justice, humanism, and democracy in Indonesian society, which has a diversity of religions, cultures, languages, and social backgrounds. This study aims to examine the content of multicultural education values ​​in the Islamic Religious Education and Character Building textbook for grade XI. The study uses a descriptive qualitative approach with a library research type. The main data was obtained from the Islamic Religious Education and Character Building textbook for grade XI, then analyzed using content analysis techniques combined with critical analysis. The results show that the textbook contains various multicultural education values ​​reflected in the learning materials, inspirational stories, reflections, and learning evaluations. The values ​​found include tolerance (tasamuh), justice (al-‘adālah), humanism (basyariyah), and democracy (al-hurriyah). The presence of these values ​​indicates that Islamic Religious Education textbooks not only function as a medium for transferring religious knowledge, but also as a means of forming students' characters that are inclusive, moderate, and respectful of diversity in social life.